Pengaruh Pendapatan Perkapita Dan Tingkat Suku Bunga Serta Inflasi Terhadap Konsumsi Rumah Tangga Samarinda - Erlina Indar Wati; Priyagus Priyagus; Muhammad Awaluddin (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
The research entilted “the effects of per capita income and interest rates and inflation on consumsi house stairs Samarinda”. It aims to find out about the per capita income variable, interest rates and inflation against domestic cosumption in Samarinda during the research year. As for the data used in this study is secondary data taken from the bank of Indonesia (BI) and central statistics agency (BPS).In the research, the secondary data is collapsed time or the the time series, analyzed using a multiple regression analysis tool. The hypothetically testing uses classical assumption test, test R and R2, which have already adapted the F and T and quantitaive analysis using the computer SPSS program 21.The study shows that per capita income has a positive and significant, effect on interest rates and inflation but is not significantly by home consumption of Samarinda.